From the crisis of the state to the crisis of the society: socio-political and routine life of Perm province in the first half of 1919 - A. V. Dolgova (Омский научный вестник: Серия "Общество. История. Современность")
The article analyzes the socio-political and routine life of the Perm province in the first half of 1919. Particular attention in the research is given to the restoration of local authorities and the people’s militia, which has not received full coverage in historiography. The purpose of the work is to study the results of the influence of the administrative activities of these authorities on the life of society, relying on unpublished sources from the funds of the State Archives of Perm Region, introduced into scientific circulation for the first time – reports of the Perm city police, reports of the chief of the Ekaterinburg police, incident reports, reports of district managers to the Governor of Perm province, orders for the Perm garrison. The theoretical basis of the research is a combination of institutional and anthropological approaches with methods of content analysis, problem-chronological and statistical. Based on the results, a special role of the Governor of Perm province N. P. Chistoserdov in the socio-political life of the region in the studied period is noted, contradictions of the legal framework and personnel policy of local authorities are highlighted; the relations between the acute crisis of the routine life against the background of the state political destabilization and the moral decay of society is emphasized.